One-Step Enrichment of Intact Glycopeptides From Glycoengineered Chinese Hamster Ovary Cells - Yang, Ganglong; Höti, Naseruddin; Chen, Shao-Yung; Zhou, Yangying; Wang, Qiong; Betenbaugh, Michael; Zhang, Hui (Frontiers in Chemistry, 2020)
Recently, the glycoproteomic analysis of intact glycopeptides has emerged as an effective approach to decipher the glycan modifications of glycoproteins at the site-specific level. A rapid method to enrich intact glycopeptides is essential for the analysis of glycoproteins, especially for biopharmaceutical proteins. In this study, we established a one-step method for the rapid capture of intact glycopeptides for analysis by mass spectrometry. Compared to the conventional sequential enrichment method, the one-step intact glycopeptide enrichment method reduced the sample preparation time and improved the detection of intact glycopeptides with long sequences or non-polar amino acids. Moreover, an increased number of glycosite-containing peptides was identified by the one-step method compared with the sequential method. When we applied this method to the glycoproteomic analysis of glycoengineered Chinese hamster ovary (CHO)-K1 cells with α1,6-fucosyltransferase (FUT8) knockout, the results showed that the knockout of FUT8 altered the overall glycosylation profile of CHO-K1 cells with the elimination of core fucosylation and together with increases in high-mannose and sialylated N-glycans. Interestingly, the knockout of the FUT8 also appeared to regulate the expression of glycoproteins involved in several functions and pathways in CHO-K1 cells, such as the down-regulation of an intracellular lectin LMAN2 showing cellular adaptation to the alterations in FUT8 knockout cells. These findings indicate that the site-specific characterization of glycoproteins from glycoengineered CHO-K1 cells can be achieved rapidly using the one-step intact glycopeptide enrichment method, which could provide insights for bio-analysts and biotechnologists to better tailor therapeutic drugs.